Dual Pathways of e-WOM toward Perceived Marketing Performance through Brand Reputation and FOMO in Social Commerce - Fitri Yutika (International Journal of Management Science and Information Technology, 2026)
The rapid growth of social commerce has transformed electronic word-of-mouth (e-WOM) into a critical factor influencing consumer perceptions and business outcomes. This study aims to examine the influence of e-WOM on Perceived Marketing Performance through the mediating roles of Brand Reputation and Fear of Missing Out (FOMO) within the TikTok Shop ecosystem. Drawing on Signaling Theory and the Resource-Based View (RBV), the study proposes a dual-pathway framework consisting of a cognitive-rational pathway represented by Brand Reputation and an affective-social pathway represented by FoMO. A quantitative research design was employed using a survey method. Data were collected from 245 TikTok Shop users in Indonesia through a structured questionnaire and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results indicate that e-WOM significantly influences both Brand Reputation and FOMO. Furthermore, Brand Reputation and FOMO were found to have significant positive effects on Perceived Marketing Performance. Mediation analysis reveals that both variables significantly mediate the relationship between e-WOM and Perceived Marketing Performance. However, Brand Reputation emerged as the dominant mediating mechanism, exhibiting a substantially stronger indirect effect than FOMO. The findings suggest that while emotional triggers contribute to consumer evaluations, reputation-based assessments remain the primary mechanism through which e-WOM translates into perceptions of marketing effectiveness.  Theoretically, this study advances social commerce research by integrating cognitive and affective pathways into a unified framework. Practically, the findings suggest that social commerce practitioners should prioritize long-term brand reputation management over short-term promotional hype, utilizing e-WOM to reinforce credibility while selectively employing FOMO-driven tactics during live-stream shopping events.